Environmental management practices of selected hotels in Metro Manila - Tabucol, Olivia Barbosa (College of Home Economics, University of the Philippines Diliman, 2013)
This study had identified he different environmental management practice (EMPs) of the five hotels in Metro Manila. Specifically, this paper covered the hotels' energy and water consumption, solid waste and waste water management, as well as air pollution. The research method is a descriptive survey using a purposive sampling to arrive at a number of respondents who are managers and rank and file employees from the subject hotels. A correlation-coefficient or Pearson R at 0.05 level of significance was used to associate the relationship between the hotels' EMPs and their various ways of communicating these EMPs to their employees. The prevailing environmental practices of the subject hotels focused on reducing solid waste management and energy and water consumption.These practices are the important initiatives of the subject hotels to reduce the impact of their operation on the environment and demonstrate commitments to environmental considerations and life cycle cost of EMPs. On the other hand, the prevailing EMPs among the food and beverage outlets inside these hotels are segregation of wastes at the source and proper forecasting and inventory of food items to avoid improper disposal of unconsumed materilas. The study revealed that the latter were not influencial factors to their green initiatives. However, their orientations, training programs, continuing education and motivational benefits can make them more environmentaly concerned, thus improving their organizational involvement and commitment towards their environmental management practices. Furthermore, this study looked into the perceived objectives and challenges of adopting environmental management practices. Achieving the goal of company-wide total environmental quality and having specific strategies to meet customers' needs were the two leading perceived benefits on EMPs. On the one hand, the three leading challenges of implementing a sound and effective EMPs were the high cost of adopting EMPs,it runs contrary to the image being projected by the hotel,and it requires too much effort to execute it. The findings can be a source of baseline data among academe, hotel industry and concerned government agencies in developing curriculum, standardizing hotel industry policies and future environmental laws.